Comparison of Bovine Bone-Autogenic Bone Mixture Versus Platelet-Rich Fibrin for Maxillary Sinus Grafting: Histologic and Histomorphologic Study - Ocak, Hakan; KÜTÜK, NÜKHET; Demetoglu, Umut; Kutuk, Nukhet; BALCIOĞLU, ESRA; Ozdamar, Saim; ALKAN, ALPER; ALKAN, ALPER (My University, 2017)
Numerous grafting materials have been used to augment the maxillary sinus floor for long-term stability and success for implant-supported prosthesis. To enhance bone formation, adjunctive blood-born growth factor sources have gained popularity during the recent years. The present study compared the use of platelet-rich fibrin (PRF) and bovine-autogenous bone mixture for maxillary sinus floor elevation. A split-face model was used to apply 2 different filling materials for maxillary sinus floor elevation in 22 healthy adult sheep. In group 1, bovine and autogenous bone mixture; and in group 2, PRF was used. The animals were killed at 3, 6, and 9 months. Histologic and histomorphologic examinations revealed new bone formation in group 1 at the third and sixth months. In group 2, new bone formation was observed only at the sixth month, and residual PRF remnants were identified. At the ninth month, host bone and new bone could not be distinguished from each other in group 1, and bone formation was found to be proceeding in group 2. PRF remnants still existed at the ninth month. In conclusion, bovine bone and autogenous bone mixture is superior to PRF as a grafting material in sinus-lifting procedures.